Why Homeschooling? ”The Role of Parental Leadership in Choosing Homeschooling: Maximizing Children's Potential” - Pratiwi, Iqmatul; Izani, Maghfira; Wijayanti, Octy; Trianung, Teguh (Edunesia : Jurnal Ilmiah Pendidikan, 2023)
This article aims to find out what are the parents’ reasons make the decision to send their children to homeschooling. In this context of education, choosing to homeschool is an alternative for parents who want to provide more personal education and focus on their children. The decision to choose to homeschool is influenced by many factors, that parents’ beliefs about formal education, availability of resources, environmental conditions, and children’s preferences. This research method uses a qualitative approach with case studies. Where this research uses case research at institutions that provide homeschooling services, in Bogor Area. This study used interview and observation techniques, the research team conducted interviews with principals, parents, and students. These results indicate the selection of homeschooling is based on parents who understand that every child has a nature, they learn of coercion. Children have to be given comfort in learning because comfortable learning will make children not bored in learning. The teacher’s task is as a facilitator about what they need. Teachers and parents together in achieving goals tailor-made for their children, because to get there, an interview with parents is needed regarding their readiness to become partners, if parents do not cooperate with the teacher, then the school will follow up and it is not recommended to take part in the learning process.